1981
DOI: 10.1093/geronj/36.2.185
|View full text |Cite
|
Sign up to set email alerts
|

Metamemory in the Aged

Abstract: College age (mean age 20 years) and older adults (mean age 69 years) were asked to predict their memory spans and to indicate readiness to recall sets of line drawings in Experiment 1. Although no age differences were found in span prediction accuracy, clear differences were obtained in recall readiness. When given unlimited study time with sets of items matched in difficulty, young adults chose to study longer and then recalled more accurately than did older adults. In Experiment 2 the recall of a chunking an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
88
4

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(97 citation statements)
references
References 0 publications
5
88
4
Order By: Relevance
“…Two approaches have been used, including surveys to obtain students' selfreported use of testing (Carrier, 2003;Gurung, 2005;Hartwig & Dunlosky, 2012;Karpicke, Butler, & Roediger, 2009;Kornell & Bjork, 2007;Kornell & Son, 2009;McCabe, 2011;Wissman et al, 2012) and laboratory observation studies that examine how students spontaneously use testing (Bottiroli, Dunlosky, Guerini, Cavallini, & Hertzog, 2010;Karpicke, 2009;Kornell & Bjork, 2008;Kornell & Son, 2009;Murphy, Sanders, Gabriesheski, & Schmitt, 1981;Murphy, Schmitt, Caruso, & Sanders, 1987;Son, 2005). The present study uses the latter approach, but evidence from both is relevant.…”
Section: Prior Literature On Self-regulated Use Of Testing and Feedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…Two approaches have been used, including surveys to obtain students' selfreported use of testing (Carrier, 2003;Gurung, 2005;Hartwig & Dunlosky, 2012;Karpicke, Butler, & Roediger, 2009;Kornell & Bjork, 2007;Kornell & Son, 2009;McCabe, 2011;Wissman et al, 2012) and laboratory observation studies that examine how students spontaneously use testing (Bottiroli, Dunlosky, Guerini, Cavallini, & Hertzog, 2010;Karpicke, 2009;Kornell & Bjork, 2008;Kornell & Son, 2009;Murphy, Sanders, Gabriesheski, & Schmitt, 1981;Murphy, Schmitt, Caruso, & Sanders, 1987;Son, 2005). The present study uses the latter approach, but evidence from both is relevant.…”
Section: Prior Literature On Self-regulated Use Of Testing and Feedbackmentioning
confidence: 99%
“…Another method involves using a recall readiness task in which participants study a list of to-be-remembered materials until they are ready to take the test (e.g., Bottiroli et al, 2010;Murphy et al, 1981Murphy et al, , 1987. In an experiment by Bottiroli et al (2010), college students were given 20 index cards with a paired associate printed on each one, and they were instructed to learn the pairs in any way they chose.…”
Section: Prior Literature On Self-regulated Use Of Testing and Feedbackmentioning
confidence: 99%
“…Cognitive performance was not only contributed to by memory complaints (Jorm et al, 2004) Previous studies attempted to identify the association between awareness of memory deficits and severity of AD, cognitive profiles and neuropsychiatric symptoms. Several previous studies suggested that impairment of insight increased with the severity of dementia (Reisberg et al, 1985;Feher et al, 1991;Lopez et al, 1994), normal aging (Murphy et al, 1981;Bruce et al, 1982), impairments in central executive functioning (Nauta, 1971;Stuss, 1991), and hypoperfusion of right dorsolateral frontal lobe (Reed et al, 1993). The findings on the association between depression and impaired awareness of memory problems are relatively inconsistent (Feher et al, 1991;Lopez et al, 1994).…”
Section: Introductionmentioning
confidence: 98%
“…7 SMCs may reflect aspects of metamemory, as older adults monitor their own forgetting. 8 Persons with SMC may show MRI-based hippocampal atrophy, a finding also seen in MCI. 9 Finally, while Alzheimer disease (AD)-type neuropathologic changes occur years before clinical symptoms are detectable, only a few studies link SMC to neuropathology 10,11 or to biomarkers.…”
mentioning
confidence: 98%